Propuesta de procedimiento operativo estándar para reporte de sospecha de incidentes adversos (IA) y notificación de sospecha de reacciones adversas a los medicamentos (RAMS) para oficina farmacéutica, en la región La Libertad - Requejo Torres, Kelyn (2016)
In this Report of Pre Professional Practices pose, a Proposal of Standard Operating Procedure (SOP) for reporting notice of Adverse incidents(AI) and notice of adverse drug Reaction(ADR) at pharmacies , within the framework of implementation of a Management System (QMS) ISO 9001: 2008 in Pharmacies, a proposal by Angulo Alvarado P. (2010). The elaboration was divided in 6 phases: In the first phase of the establishment processes and their classification according to ISO 9001 Identified, the second included the identification of existing national laws relating to Pharmacovigilance and Pharmaceutical Technovigilance in office. Registration List of Internal and External Records and Documents, Standard Operating Procedure for Processing and Document Control, Standard Operating Procedure for reporting notice of AI and notice of suspected ADRs: In the third phase the following documents and records were made adverse Drug (RAMs). The fourth phase involved the review of the proposal by professors from the Faculty of Pharmacy and Biochemistry, National University of Trujillo and a representative of the Department of Pharmacovigilance and Technovigilance of the Regional Health Management - La Libertad. As the final phase rectification of observations was made, the final proposal presented in this report